Perancangan Sistem Informasi Akademik (SIAKAD) Berbasis Web Di SMK Negeri 1 Sijunjung - Muhammad Zulfikri Arsyad; Thomson Mary; Satrio Junaidi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
Access to academic data is crucial in the digital era and should be more efficiently managed. However, many educational institutions continue to rely on traditional data management methods, such as maintaining physical ledgers or storing information in word or excel files, which hinder accessibility and efficiency. This study aims to design, develop, and evaluate an Academic Information System to enhance data accessibility and streamline academic record management. The system is developed using the Iterative System Development Life Cycle (SDLC), which comprises four key phases: requirement analysis, system design, coding, and testing. These phases are repeated iteratively until the system meets the required functional and usability standards. The Laravel framework was using to enhance structural integrity and security during the coding phase. Beta testing conducted by experts produced an average score of 98.67%, with the highest criteria ratings observed in functionality, efficiency, and maintainability, each scoring 100% and categorizing this criteria as highly satisfactory. Meanwhile, end-user testing yielded an average user satisfaction score of 87.78%, with usability receiving the highest rating at 90.63%, also classified as highly satisfactory. Based on the testing data, these study resulted in an academic information system that capable of improving data management and undergone a series of testing.